Diversity and Dominance of Insects on Various Types of Fruit Plants Using the Yellow Trap Method in Agricultural Land in Bangko Village, West Halmahera Regency - Sabban, Helda; Kadir Lahati, Betty (Jurnal Agroekoteknologi Terapan, 2025)
This study analyzed insect diversity and dominance in fruit agroecosystems at Bangko Village, Khairun University Campus IV. From 40 yellow traps, 1,820 individuals were recorded on bananas (10 orders, 15 families) dominated by Erionata trax, and 1,259 individuals on pineapples (9 orders, 13 families) dominated by Formicidae ants. The diversity index was moderate (H’=2.66 on bananas; H’=2.25 on pineapples) with low dominance, indicating no single species dominated. Keywords: Yellow Trap, Insect diversity, Harticulture Abstrak Penelitian ini menganalisis keanekaragaman dan dominansi serangga pada agroekosistem buah di Desa Bangko, Kampus IV Universitas Khairun. Dari 40 perangkap kuning, tercatat 1.820 individu pada pisang (10 ordo, 15 famili) dengan dominansi Erionata trax, serta 1.259 individu pada nanas (9 ordo, 13 famili) didominasi semut Formicidae. Indeks keanekaragaman tergolong sedang (H’=2,66 pada pisang; H’=2,25 pada nanas) dengan dominansi rendah, menunjukkan tidak ada spesies yang mendominasi. Kata Kunci: Perangkap Kuning, Keanekaragaman Serangga, Hortikultura